'Lonely': education policies and their reception, between indigestible carrots and demands for proper regulation. Issue 2 (3rd April 2022) - Malandrino, Anna
ABSTRACT: Italy's education policy prioritized two main areas of action during the second year of the Covid-19 pandemic: mitigating the health impact of the crisis on students and educators, and implementing public policies that ensure the proper functioning of the country's education system in view of a return to normalcy. In this article, I analyse education-policy decisions and non-decisions with a focus on their reception by the school personnel system. The analysis engages with the classical literature on public policy, distinguishing between 'carrots' and 'sticks' as instruments for policy change. I argue that the health crisis has revealed structural weaknesses that underlie the country's education policy and politics. Through an analysis of the policy actors' reactions to those decisions (and non-decisions), I show that a pattern of prolonged oversight by the national government has provoked an appetite not only for financial measures, but also for more policy regulation. The analysis underscores the dual need for 1) well-defined rules and policy regulations that allocate a clearer division of responsibilities, and 2) greater involvement by the national government in the area of post-pandemic education reform.